A survey of adaptive large neighborhood search algorithms and applications - Mara, Setyo Tri Windras (Elsevier, 2022)
This article provides a survey on the highly popular metaheuristic framework, the adaptive large neighborhood search (ALNS). The basic concepts of ALNS are discussed in this paper. Based on a simple taxonomy, the analysis of publication intensity, application areas, and the variant of ALNS features are executed on 252 scientific publications to synthesize the state-of-the-art of ALNS research. Finally, some discussions on the future research of ALNS are provided